2006
DOI: 10.5194/bg-3-147-2006
|View full text |Cite
|
Sign up to set email alerts
|

Biological control of the terrestrial carbon sink

Abstract: Abstract. This lecture reviews the past (since 1964 when the International Biological Program began) and the future of our understanding of terrestrial carbon fluxes with focus on photosynthesis, respiration, primary-, ecosystem-, and biomeproductivity.Photosynthetic capacity is related to the nitrogen concentration of leaves, but the capacity is only rarely reached under field conditions. Average rates of photosynthesis and stomatal conductance are closely correlated and operate near 50% of their maximal rate, Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
122
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(127 citation statements)
references
References 57 publications
3
122
0
2
Order By: Relevance
“…We have also shown that the particular traits selected here, specific leaf area, leaf dry matter content, leaf area, and mature plant height, could be used to capture the functioning of plant species and communities. Our observations also promote a better understanding of plant-soil feedbacks related to plant functional traits in plant communities, but longterm monitoring is needed in future research, especially in different times of the year, because the cycling and sequestration of soil nutrients may be a "fast-out, slow-in" process with high variation due to regulation by environmental factors (Schulze, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…We have also shown that the particular traits selected here, specific leaf area, leaf dry matter content, leaf area, and mature plant height, could be used to capture the functioning of plant species and communities. Our observations also promote a better understanding of plant-soil feedbacks related to plant functional traits in plant communities, but longterm monitoring is needed in future research, especially in different times of the year, because the cycling and sequestration of soil nutrients may be a "fast-out, slow-in" process with high variation due to regulation by environmental factors (Schulze, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…anthropogenic emissions and, on a global scale, it has been estimated that the terrestrial biosphere is able to take up about 30 % of anthropogenic CO 2 emissions annually (Schulze, 2006;Canadell et al, 2007).…”
Section: Zanotelli Et Al: Carbon Fluxes In An Apple Orchardmentioning
confidence: 99%
“…Thus, there is a need for better understanding on how tissue and whole-plant respiration rates are affected by elevated CO 2 (i.e. from current ambient to doubling ambient levels), as small changes in terrestrial plant respiration could have a significant impact on the annual increment in atmospheric CO 2 concentration (Valentini et al, 2000;Gonzalez-Meler et al, 2004;Schulze, 2006).…”
mentioning
confidence: 99%